2022
DOI: 10.31486/toj.21.0138
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antepartum Factors for Predicting the Risk of Emergency Cesarean Delivery in Pregnancies Complicated With Placenta Previa

Abstract: Background:The optimal delivery timing for patients with placenta previa remains controversial in the literature. To reduce spontaneous vaginal bleeding rates, which occur increasingly with advancing gestational weeks, elective cesarean delivery is advocated between 36 0/7 and 37 6/7 weeks of gestation, but this clinical approach does not take into consideration numerous patient variables. Few papers identify the risk factors for emergency cesarean delivery in patients with placenta previa. An enhanced underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 28 publications
1
18
1
Order By: Relevance
“…Six studies reported the numbers of newborns with a low Apgar score (<7), instead of the means, at 5 minutes after birth. [18,19,21,23,28,34] When delivered by emergency, neonates had a higher likelihood of having a low 5-minute Apgar score (OR: 0.27; 95% CI: 0.11–0.69; P = .01; I 2 = 65%) (Fig. 2E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies reported the numbers of newborns with a low Apgar score (<7), instead of the means, at 5 minutes after birth. [18,19,21,23,28,34] When delivered by emergency, neonates had a higher likelihood of having a low 5-minute Apgar score (OR: 0.27; 95% CI: 0.11–0.69; P = .01; I 2 = 65%) (Fig. 2E).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies compared the birth weights between the PCD and ECD groups. [16][17][18][19][20][21][22][23][24][25]27,28,33] However, one study [16] reported the medians of birth weight in 3 gestational ranges and therefore could not be pooled. In comparison to the ECD group, the pooled birth weight was significantly higher in the PCD group (SMD: 1.64; 95% CI: 1.00-2.27; P < .001; I 2 = 97%).…”
Section: Neonatal Birth Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…Rupture of membranes before 37 th gestational week was designated as PPROM [13]. Pregnant women with gestational diabetes mellitus [14] who had a positive oral glucose tolerance test were excluded from the study, but pregnant women with placenta previa [15] were included. In our study, the normal ranges for TSH, T4, and anti-TPO levels were considered 0.1-2.5 mIU/L, 0.93-1.71 ng/dl, and <5.60 IU/mL, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Repeated CDs are associated with additional risks, including difficulties in surgical dissection, placenta previa, abnormal placental invasion, and peripartum hysterectomy. These complications could be life-threatening for both the pregnant woman and the baby (11,12). However, it remains uncertain whether the frequency of adverse outcomes differs with increasing numbers of CDs.…”
Section: Introductionmentioning
confidence: 99%